Protective effect of sterubin against neurochemical and behavioral impairments in rotenone-induced Parkinson's disease - M.M. Alqurashi; F.A. Al-Abbasi; M. Afzal; A.M. Alghamdi; M. Zeyadi; R.A. Sheikh; S. Alshehri; S.S. Imam; N. Sayyed; I. Kazmi (Brazilian Journal of Medical and Biological Research, 2024)
This study was conducted to evaluate how sterubin affects rotenone-induced Parkinson's disease (PD) in rats. A total of 24 rats were distributed into 4 equal groups: normal saline control and rotenone control were administered saline or rotenone (ROT), respectively, orally; sterubin 10 received ROT + sterubin 10 mg/kg po; and sterubin alone was administered to the test group (10 mg/kg). Rats of the normal saline and sterubin alone groups received sunflower oil injection (sc) daily, 1 h after receiving the treatments cited above, while rats of the other groups received rotenone injection (0.5 mg/kg, sc). The treatment was continued over the course of 28 days daily. On the 29th day, catalepsy and akinesia were assessed. The rats were then euthanized, and the brain was extracted for estimation of endogenous antioxidants (MDA: malondialdehyde, GSH: reduced glutathione, CAT: catalase, SOD: superoxide dismutase), nitrative (nitrite) stress markers, neuroinflammatory cytokines, and neurotransmitter levels and their metabolites (3,4-dihydroxyphenylacetic acid (DOPAC), dopamine (DA), norepinephrine (NE), serotonin (5-HT), 5-hydroxyindoleacetic acid (5-HIAA), and homovanillic acid (HVA)). Akinesia and catatonia caused by ROT reduced the levels of endogenous antioxidants (GSH, CAT, and SOD), elevated the MDA level, and altered the levels of nitrites, neurotransmitters, and their metabolites. Sterubin restored the neurobehavioral deficits, oxidative stress, and metabolites of altered neurotransmitters caused by ROT. Results demonstrated the anti-Parkinson's activities of sterubin in ROT-treated rats.